ANALISIS MAKNA ADVERBIA TABI TABI, SHIBA SHIBA DAN YOKU DALAM BAHASA JEPANG - Putryani, Helen; Astuti, Sri; Wiyatasari, Reny (Japanese Literature, 2016)
Adverbial Tabi Tabi, Shiba Shiba and Yoku have the same meaning, which is a repeatof an event or condition (often). The third adverbial above has different frequencylevels. Adverbial of Tabitabi has higher frequency levels than adverbial ofShibaShiba but adverbial of Tabitabi is lower than adverbial of Yoku. Adverbial ofShibaShiba is the lowest levels of frequency and adverbial of Yoku is the highestfrequency levels.